Analisis Spasial Kejadian Malaria Dan Habitat Larva Nyamuk Anopheles spp di Wilayah Kerja Puskesmas Winong Kabupaten Purworejo - Resiany Nababan; Sitti Rahmah Umniyati (Berita Kedokteran Masyarakat (BKM), 2018)
Environmental and behavioral factors affecting malaria cases in high endemic area of Central Java: a geographic information system analysisPurposeThis research aimed to analyze risk factors involved in malaria cases, to map the spatial distribution of malaria cases related to breeding habit to location spacing and to know the habitat of Anopheles sp.  mosquito larvae near the  the public health center of Winong, district of Purworejo.MethodThis research was a case control study using data through the geographic information system.ResultsTemperature, humidity and rainfall variables had no correlation with malaria incidence. There were correlations between malaria incidence with the existence of breeding habitat, house wall condition and nighttime habit, whereas the presence of livestock, breeding site distance, the habit of wearing mosquito nets, the use of wire mesh, the use of mosquito repellent and the habit of visiting endemic areas had no correlation with malaria incidence. Night-outside habits were the highest risk factors associated with malaria incidence.ConclusionThere was no correlation between weather factors and malaria incidence. There was a correlation between the presence of larval breeding habitat, the condition of the wall of the house and the habit of going out at night with the incidence of malaria. There are 3 clusters in the work area of public health center in Winong and most cases are in the buffer zone area 1000 m distance.